The influences of ionic liquid to the properties of poly(ethylmethacrylate) based electrolyte - Zain, N.F.; Zainal, N.; Mohamed, N.S. (IOP Publishing, 2014)
A new and thermally stable poly (ethyl methacrylate) incorporated with 1-ethyl-3-methylimidazolium bis(trifluorosulfonyl) imide ionic liquid electrolytes were prepared using solution casting technique. Interaction between the polymer and ionic liquid was confirmed by Fourier transform infrared spectroscopy. The presence of amorphous phase which increased with increasing ionic liquid content was observed from scanning electron microscopic analysis. This result can be correlated to the decreased in glass transition temperature and the melting point of the sample obtained from differential scanning calorimetry. The addition of EMITFSI in PEMA matrix improved the thermal stability of the polymer electrolytes up to approximately 300 °C. The sample showed a maximum conductivity of 9.75 × 10-5 S cm-1 at 100 °C with activation energy value of 0.69 eV. The result obtained from linear sweep voltammetry revealed that the electrolyte system exhibited a reasonably wide electrochemical window.